2017
DOI: 10.1037/rev0000076
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic approach to recognition memory.

Abstract: ii Acknowledgements First, I extend my thanks to my committee members for their time, consideration, and guidance. I would especially like to thank my advisors, Rich Shiffrin and Mike Jones, for first convincing me to come to Indiana, making me feel welcome, and guiding me into the world I now inhabit. I must also thank Isaiah Harbison, Michael Dougherty, and Sharona Atkins for introducing me to the very idea of mathematical psychology and for teaching me and trusting me. show how the dynamic model can be exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 307 publications
(629 reference statements)
5
81
0
2
Order By: Relevance
“…This similarity could arise either because items and associations are encoded using similar information or because the processes used to retrieve item and associative information are related, or both. We are not in a position to adjudicate this question here, although we note that other work from our laboratory supports the idea that item and associative information are both stored and retrieved using similar processes (Cox & Criss, 2017), and that memory for associative information involves elaborating or interrelating information about items (Cox & Shiffrin, 2017;see also McGee, 1980;Dosher, 1984;Dosher & Rosedale, 1989, 1991, 1997. Consistent with the idea that item and associative information are encoded in a similar manner, we found that the same item properties, like concreteness and semantic specificity, that make a single word easy to recognize (and to reject when unstudied) also make it easy to recognize a pair in which that word appears.…”
Section: Theoretical Implicationsmentioning
confidence: 79%
See 3 more Smart Citations
“…This similarity could arise either because items and associations are encoded using similar information or because the processes used to retrieve item and associative information are related, or both. We are not in a position to adjudicate this question here, although we note that other work from our laboratory supports the idea that item and associative information are both stored and retrieved using similar processes (Cox & Criss, 2017), and that memory for associative information involves elaborating or interrelating information about items (Cox & Shiffrin, 2017;see also McGee, 1980;Dosher, 1984;Dosher & Rosedale, 1989, 1991, 1997. Consistent with the idea that item and associative information are encoded in a similar manner, we found that the same item properties, like concreteness and semantic specificity, that make a single word easy to recognize (and to reject when unstudied) also make it easy to recognize a pair in which that word appears.…”
Section: Theoretical Implicationsmentioning
confidence: 79%
“…This factor identifies a trade-off between two sets of parameters in associative recognition: boundary separation and drift, on the one hand, versus residual time and bias on the other. While we again do not wish to over-interpret this factor, we note that in the model proposed by Cox and Shiffrin (2017), item information tends to be retrieved earlier than associative information, such that the information needed to distinguish between intact and rearranged pairs in AR is only available later in retrieval. As a result, accumulating evidence earlier-which would correspond to a shorter residual time prior to the onset of evidence accumulation-would yield more positive recognition evidence-higher drift rate-because the items in both intact and rearranged pairs had been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, the mapping of early stimulus components onto within-trial variability and late decision components onto between-trial drift rate variability may not be so clear. For example, see some recently developed dynamic models of memory (Cox & Shiffrin, 2017). There is a principled reason to assume that within-trial drift rate variability is…”
Section: Evidence For Variability In Drift Ratementioning
confidence: 99%